Peyek and Social Change: An Analysis of Peyek's Impact on Cultural Identity and Da'wah in Yogyakarta - Suroyo, Suroyo; Putra, Bima Maulana; Fredyarini Soedjiwo, Novena Ade; Adnan, Fatmahwati (Journal of Islamic History and Manuscript, 2025)
Scholars consider Peyek, a typical Javanese light meal, to have deep cultural and religious significance. People believe Peyek represents thankfulness, prosperity, and past benefits, connecting it to Wali Songo’s efforts to spread Islam across Java. This research study investigates the role of peyek in cultural immersion and Islamic da'wah in Yogyakarta. Qualitative research approaches were used to learn about the cultural relevance and Islamic symbolism linked to peyek in Yogyakarta. The Mataram Sultanate region, encompassing the districts of Kota Gede, Tugu Yogyakarta, Malioboro, Kraton Yogyakarta, and Krapyak Stage, was the major focus of the study, which was supplemented with insights from notable peyek markets such as Gamping, Ngasem, and Kranggan. The major research technique used was direct observation, and the study found that peyek is important in solidifying both the cultural heritage and religious beliefs in Yogyakarta. It appears to serve as a conduit for the development of belief and the promotion of local cultural identity through Islamic da'wah efforts, including local cultural components with Islamic preaching to strengthen Yogyakarta's cultural identity and promote religious harmony.